PENGEMBANGAN KIT PEMBELAJARAN DARI LIMBAH SEKAM PADI PADA MATERI BENTUK MOLEKUL KELAS X SMA - Adelia Yesya Putri Hasibuan; Iis Siti Jahro (Universitas Negeri Medan, 2020)
Learning media has a very important role because it can increase motivation, improve understanding and retention of learning. But the reality in school learning media is often overlooked for reasons of diffuclty finding the right media and limited time to make it yourself. To overcome the nothingness of learning media on molecular shape material, learning media from rice husk waste are developed. This study aims: (1)To know the feasibility of KIT learning media which used in learning activities. (2)To know student learning outcomes by using KIT learning media is higher than KKM. (3)To know student learning activities by using KIT learning media. This type of research is development of ADDIE research model carried out in class XI MIA 2 SMA Swasta Budisatrya Medan. The results of the research are: (1)KIT Learning on molecular shape material has been developed is feasible for use and is in accordance with Ministry of Education and Culture standards with a percentage of 96.87%. (2)Student learning outcomes that use KIT learning media on molecular shape material are higher than KKM. (3) Student learning activities using KIT learning media on molecular shape materials reach the criteria of Good with an average value of 90.